AC REPAIR SERVICE SYSTEM ON PT. IGLOO NUANSA SEGAR - Intan Novianti; Don Elsafitra, SKom (Jurnal Sistem Informasi, 2000)
Use tools such as computers in the present is not foreign to the advancement of industry and technology. And also very menbantu a company big enough money such as PT.  IGLOO. With a computerized system of data that has been recorded can be processed into a useful information that will in the future required a lot of parties.  With this system PT. IGLOO in the input of customer data will become very efficient and effective when compared to the use of recording into a book which is a manual system. The new system is Visual Basic 5.0 application software is difficult for a beginner. However, when compared with other applications, this application further to minimize the writing program, thus simplifying the use of the program, coupled with the tools contained in this application makes the program look  interesting.